Combined heterogeneous distribution of salt and aroma in food enhances salt perception - Emorine, Marion; Septier, Chantal; Andriot, Isabelle; Martin, Christophe; Salles, Christian; Thomas-Danguin, Thierry (Food & function, 2015)
Aroma-taste interactions and heterogeneous spatial distribution of tastants were used as strategies for taste enhancement. This study investigated the combination of these two strategies through the effect of heterogeneous salt and aroma distribution on saltiness enhancement and consumer liking for hot snacks. Four-layered cream-based products were designed with the same total amount of sodium and ham aroma but varied in their spatial distribution. Unflavoured products containing the same amount of salt and 35% more salt were used as references. A consumer panel ( n = 82) rated the intensity of salty, sweet, sour, bitter and umami tastes as well as ham and cheese aroma intensity for each product. The consumers also rated their liking for the products in a dedicated sensory session. The results showed that adding salt-associated aroma (ham) led to enhancement of salty taste perception regardless of the spatial distribution of salt and aroma. Moreover, products with a higher heterogeneity of salt distribution were perceived as saltier ( p < 0.01), whereas heterogeneity of ham aroma distribution had only a marginal effect on both aroma and salty taste perception. Furthermore, heterogeneous products were well liked by consumers compared to the homogeneous products. Combining salt and aroma heterogeneous distribution in hot snacks improves saltiness perception and helps to maintain consumer liking. This approach is relevant for lowering salt content in food.